Upaya Pencegahan Dan Pengendalian Hipertensi Melalui Penyuluhan Kesehatan Dan Kegiatan Senam Hipertensi Pada Lansia Didusun Ll Desa Pekik Nyaring,Kab Bengkulu Tengah - Nurfadilah, Siski; Lestari, Susi; Khairunisa, Miska; Wulandari, Wulandari; Surahman, Feri (Universitas Dehasen Bengkulu, 2024)
Hypertension is an increase in blood pressure in the arteries. Where Hyper means excessive, and Tensi means pressure/tension, so hypertension is a disorder of the blood circulation system which causes an increase in blood pressure above normal values (Musakkar & Djafar, 2021). The method in this research uses lecture and question and answer methods. The results and discussion show that before and after the counseling there was an increase in good knowledge from 23% to 69%, while for the lack of criteria there was a change from 74% to 31%. Conclusions and suggestions Can provide knowledge about hypertension and carry out hypertension exercise activities for the elderly.